2020
DOI: 10.1021/acs.jafc.0c03223
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Krill Derived Nonapeptide as an Effective Iron-Binding Ligand for Facilitating Iron Absorption via the Small Intestine

Abstract: A novel nonapeptide DTDSEEEIR identified from Antarctic krill (Euphausia superba) iron-binding peptides was used in this study to analyze its iron-binding sites and structural changes after iron coordination. The enzymatic resistance and transport of DTDSEEEIR–iron during gastrointestinal digestion and absorption as well as the relationship between the DTDSEEEIR stability and the enhancement of iron absorption were further explored. Results revealed that iron ions spontaneously bound to the carboxyl, hydroxyl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…The zinc transport rate of RPKHPLSHDL‐Zn and RPKHPLK‐Zn was significantly higher than that of ZnSO 4 . The absorption experiment of iron‐chelating peptide also suggested that the iron uptake of the chelates was higher than that of FeSO 4 alone (Sun et al., 2020; T. Wang et al., 2020). Between 90 and 120 min, both RPKHPLSHDL‐Zn and RPKHPLK‐Zn showed the highest increase rate in zinc transport, 40.37% and 33.70%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The zinc transport rate of RPKHPLSHDL‐Zn and RPKHPLK‐Zn was significantly higher than that of ZnSO 4 . The absorption experiment of iron‐chelating peptide also suggested that the iron uptake of the chelates was higher than that of FeSO 4 alone (Sun et al., 2020; T. Wang et al., 2020). Between 90 and 120 min, both RPKHPLSHDL‐Zn and RPKHPLK‐Zn showed the highest increase rate in zinc transport, 40.37% and 33.70%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More zinc ions can be attracted to the highly anionic peptide surface (Udechukwu et al., 2018). Iron binding activity of Antarctic krill derived peptides was positively correlated with the concentration of amino acids with negative net charge, while negatively correlated with that of positively charged amino acids (Sun et al., 2020). In fact, the isoelectric points of the two peptides were 11.67 and 9.77, respectively, based on the software simulating results (not listed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was performed according to Sun and Lin 24 with some modifications. Sprague–Dawley (SD) rats (male, weighing 150–200 g) were obtained from Dalian Medical University, China.…”
Section: Methodsmentioning
confidence: 99%
“…XPS instrument measures the kinetic energy emitted from surface elements upon X-ray exposure. It has been used to characterize the binding of iron to an Antarctic krill derived peptide (38). Since each of our PSPH samples is a mixture of peptides with different molecular weights, the XPS was only used quantitatively to identify the PSPH-Zn.…”
Section: X-ray Photoelectron Spectroscopy Spectra Of Psph and Psph-znmentioning
confidence: 99%